Relationship Between Motivation and Intention to Practice Physical Activity. A Comparative Study Among Spanish and Argentinian Adolescents - Franco Álvarez, E.; Coterón López, J.; Gómez, V.; Laura de Franza, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
The aim of the present work is to study differences in motivational orientation, intrinsic motivation, current physical activity and intention to be physically active between students from Argentina and from Spain, as well as to analyze the influence that the first three of these variables have on the last one. Some validated questionnaires were administered to a sample composed of 1597 physical education students from Argentina and Spain aged 14 to 18. Results suggest slightly differences between subjects from both of the participants’ countries while regression analyses reveal the emergency of intrinsic motivation and current physical activity as the main predictors of the intention to be physically active in both contexts. Results are discussed from the tenets of the main theories which have been considered in the study of motivation within physical activity settings and in the framework of other cross-cultural studies.